Manajemen Sarana dan Prasarana Sekolah dalam Meningkatkan Mutu Pendidikan di MTs Al-Ihsan Kalikejambon Tembelang Jombang - Fatimah, Dewi; Sirojudin, Didin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Facilities and infrastructure are very important for education in schools. With good management, facilities and infrastructure can improve the quality of learning. The purpose of this research is to understand the management of facilities and infrastructure to improve the quality of education at MTs Al-Ihsan. The method used in this research is descriptive qualitative. The data sources used in this research are primary data sources and secondary data sources. To obtain the data needed in the study, researchers used observation, interview, and documentation methods. The results of this study indicate that the management of school facilities and infrastructure at MTs Al-Ihsan, namely (1) planning is done by making a madrasah and school budget every year. Organizing is controlled by the vice principal with the aim of creating a safe, comfortable learning environment and supporting the optimal educational process. Implementation is carried out in a planned and structured manner, with a comprehensive evaluation of the condition of infrastructure facilities every year. Supervision is carried out regulary by the principal and the vice principal of infrastructure facilities, by maintaining security and preventing the loss of goods. (2) The obstacle is the limited funds. And the solution is to seek grants from foundations, funds from BOS and BOSDA, approach political parties, candidates, DPR to obtain greater funding assistance. (3) Efforts to develop facilities and infrastructure are by repairing buildings, adding book collections, laboratory equipment and equipment.